Cardiovascular risk profile in master Paralympic athletes, a high-risk undertreated population: A cross-sectional longitudinal study - Di Gioia, G.; Vespasiano, F.; Mango, F.; Maestrini, V.; Monosilio, S.; Squeo, M. R.; Lemme, E.; Bernardi, M.; Pelliccia, A. (High Blood Pressure & Cardiovascular Prevention, 2024)
Introduction Recently, European Society of Cardiology (ESC) validated a prediction model to estimate 10-year fatal and non-fatal cardiovascular disease risk (CVDR) in individuals (aged 40-60 years) without previous cardiovascular disease or diabetes (ESC-SCORE2) and to provide indications for treatment. At present, data describing the CVDR in Paralympic athletes (PAs) are scarce and inconsistent. Therefore, we sought to assess the prevalence of risk factors in PAs to estimate their CVDR through SCORE2.